Estimating the need for PhDs in the academic sector via a survey of employers - Jaan Masso; Raul Eamets; Hanna Kanep (Institute for the Study of Labor (IZA), 2007)
The aim of the current paper is to estimate the need for new PhDs in the Estonian academic sector for the 5-year period 2007-2012 using a survey of employers, such as universities, institutions of applied higher education and research institutes. The doctoral workforce in all countries around the world constitutes a rather small segment of the labour market; however, PhDs provide a crucial input for educational and R&D activities not only through their employment in the academic sector, but nowadays also increasingly in the public and private sector. Our results show that academic institutions would prefer to hire a rather high proportion of new PhDs - almost 100% of the current number. On the one hand total demand is high due to a high replacement demand brought on by retirements in the next years as a result of the current unfavourable age structure of the doctoral workforce. Still, the growth demand constitutes more than 50% of the total demand. Such growth, in our view, assumes significant growth in research funding, which the respondents mostly did not believe would occur, despite it having been foreseen in national R&D policy documents. In general, the respondents seemed to see the problem being the lack of PhDs rather than the lack of funding. The policy implication of our results is that the planned increase in the numbers of PhDs should be in accordance with other developments in educational and R&D policy.
Keywords: 330; PhD; higher education; research and development; academic fields; Akademische Berufe; Hochschule; Forschung; Estland